2012
DOI: 10.5588/ijtld.10.0600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the GenoType® MTBDRsl assay for susceptibility testing of second-line anti-tuberculosis drugs

Abstract: Background: The GenoType® MTBDRsl assay (Hains, Lifesciences, Germany) is a new rapid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Controversies regarding sensitivity rates of the assay reported in previous studies, especially for AGs and CPs and for KAN in particular (15,16,(21)(22)(23), could be attributed to the diverse genetic background of strains and different distribution of mutations conferring drug resistance in different geographic settings. In recent studies conducted on clinical strains isolated in Estonia, Vietnam, and South Africa, the sensitivity of the assay for the detection of resistance to KAN was very low (reaching 43% at its maximum) (16,22,23), probably due to the high prevalence of Beijing strains harboring mutations in eis genes not recognized by the assay and responsible for conferring resistance to KAN only, as was shown in Vietnam (23).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Controversies regarding sensitivity rates of the assay reported in previous studies, especially for AGs and CPs and for KAN in particular (15,16,(21)(22)(23), could be attributed to the diverse genetic background of strains and different distribution of mutations conferring drug resistance in different geographic settings. In recent studies conducted on clinical strains isolated in Estonia, Vietnam, and South Africa, the sensitivity of the assay for the detection of resistance to KAN was very low (reaching 43% at its maximum) (16,22,23), probably due to the high prevalence of Beijing strains harboring mutations in eis genes not recognized by the assay and responsible for conferring resistance to KAN only, as was shown in Vietnam (23).…”
Section: Discussionmentioning
confidence: 92%
“…In recent studies conducted on clinical strains isolated in Estonia, Vietnam, and South Africa, the sensitivity of the assay for the detection of resistance to KAN was very low (reaching 43% at its maximum) (16,22,23), probably due to the high prevalence of Beijing strains harboring mutations in eis genes not recognized by the assay and responsible for conferring resistance to KAN only, as was shown in Vietnam (23). Absence of cross-resistance to AMK and CAP in strains harboring mutations in the eis promoter region has been recently demonstrated in a genomic study of resistance in Samara, Russia (24), and in another study conducted in Russia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, resistant strains can easily be judged as susceptible, when embB 306 is used as the detection target, by mistake. The specificity showed large variations among different studies in genotype GenoType MTBDRsl group and lower pooled specificity than other groups due to the low specificities (0.55, 0.56) of two included studies (29,31) with large sample sizes. In the study by Said et al (31), all of the isolates were MDR, whereas Hazbón et al (49) reported that embB 306 mutations that may be associated with MDR and that MDR isolates phenotypically susceptible to EMB carried mutations at codon 306 of the embB gene.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported a high agreement between GenoType MTBDRsl and PCR-DNA sequencing (24,25,28,31). Pyrosequencing can provide the same accuracy as the sequencing method (38); thus, we considered the studies that used the three molecular assays for the detection of EMB resistance as a group in order to stratify by type of reference standard.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies in China, Vietnam, and South Africa revealed that the most frequent mutations are D94G (gyrA) (36.5%) and A1401G (rrs) (42.1%) in China, D94G (54%) and A1401G (80%) in Vietnam, and D94G (42.4%) in South Africa; these were the most frequent mutations also detected in Colombian strains (4,21,26).…”
Section: Discussionmentioning
confidence: 99%